The role of principal leadership in innovating english language learning in Indonesian elementary schools: a thematic literature review - Lisa Anna Nasution Lisa (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This thematic literature review explored how principal leadership shaped and sustained innovation in English language learning within Indonesian elementary schools. Drawing on 27 peer-reviewed studies published between 2010 and 2025, the review examined the interplay between transformational and instructional leadership models in advancing pedagogical practices. The findings highlighted that principals who fostered collaborative school cultures, invested in professional development, and strategically mobilized resources significantly enhanced teacher innovation and student engagement. However, a gap existed in the limited number of studies that linked principal leadership to English language learning innovation in Indonesian elementary school contexts, particularly in comparing public and private Islamic schools. The novelty of this study highlighted the integration of transformational and instructional leadership models in fostering English language learning innovation in Indonesian elementary school contexts, especially regarding leadership roles in driving English language innovation amid infrastructural, cultural, and policy-based constraints. The study methodologically employed thematic analysis modeled after Braun and Clarke (2006), which allowed for comprehensive identification of patterns, challenges, and strategies across school contexts. It recommended developing integrated leadership models and future empirical studies to validate leadership-driven innovations in diverse school environments.